The Role of the Governments of Indonesia and Saudi Arabia in Organizing the Hajj Pilgrimage 2015 – 2021 - Subandi, Didi; Machmudi, Yon (UI Scholars Hub, 2022)
The Hajj pilgrimage is one of the largest annual mass gatherings in the world, and has been held for a long time. This study presents an overview of a systematic research of published literature on the Role of the Governments of Indonesia and Saudi Arabia in organizing of the Hajj pilgrimage from 2015 until 2021 Period, with the aim of providing policy recommendations for the future. From this research, it can be concluded that the implementation of Hajj pilgirmage in Indonesia is strongly influenced by the bilateral relations between the two countries. This can be seen from a historical perspective, since Indonesia's independence there were quite a lot of pilgrims from Indonesia. The relationship between Indonesia and Saudi Arabia has been established from colonial era until now. In the future, bilateral relations between Indonesia and Saudi Arabia in the context of organizing the Hajj will continue to be intensified. Considering that for the past 2 years, Indonesia has not sent hajj pilgrims due to the pandemic, as well as Saudi Arabia which has not opened its doors for hajj pilgrims outside of Arabia for 2 years, Indonesia and Saudi Arabia good governance diplomacy is the solution for better implementation of the Hajj Pilgrimage in the future.